Detection and prevention of adverse drug reactions in multi-morbid older patients. (12th September 2018) - Jennings, Emma; Gallagher, Paul; O'Mahony, Denis
Abstract: Adverse drug reactions (ADRs) are a recognised unintentional form of iatrogenic harm, which commonly occur in older adults who have high levels of multi-morbidity and associated polypharmacy. Previous studies estimate that at least one in 10 hospitalised older patients will experience an ADR. While recent research indicates that this could be as high as 39% in hospitalised multi-morbid, older adults, up to two-thirds of these ADRs can be considered preventable and therefore potentially avoidable. In addition to increasing patient morbidity and contributing to avoidable mortality, there is an associated cost implication with ADR occurrence. This commentary summarises current mainstream research in terms of ADR detection, prediction and prevention in multi-morbid older patients. At present, the biggest barrier to understanding and comparing ADRs in the literature is the large heterogeneity that exists in the population and study methods. Furthermore, there is the lack of standardised universally accepted methodology for ADR prediction, detection, causality assessment and subsequent prevention in older people. Standard available methods of ADR prediction applied to a heterogeneous multi-morbid population are generally unsatisfactory. Without an instrument that consistently and reliably predicts ADR risk in a reproducible manner, ADR prevention in multi-morbid older patients is challenging. Further attention should be focused on the culprit drugs that commonly lead to major ADRs in older multi-morbid hospitalised patients with polypharmacy. Risk associated with particular drug classes may possibly predict ADR occurrence better than patient characteristics alone. Current research is examining this drug class focus for ADR prevention in multi-morbid older people.